2006
DOI: 10.1029/2005gl024606
|View full text |Cite
|
Sign up to set email alerts
|

Renormalizing chaotic dynamics in fractal porous media with application to microbe motility

Abstract: Motivated by the need to understand the movement of microbes in natural porous systems and the evolution of their genetic information, a renormalization procedure for motile particles in media with fractal functionality between upper and lower cutoffs is developed and applied to Lévy particles. On the micro scale, particle trajectories are the solution to an integrated stochastic ordinary differential equation (SODE) with Markov, stationary, ergodic drift subject to Lévy diffusion. The Lévy diffusion allows fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In subsequent analysis we model the meso scale drift in two ways. The first parallels that of [10,11] with the Lagrangian velocity a-stable Lévy. The second and novel approach is to model the Lagrangian mesoscale acceleration as a-stable Lévy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In subsequent analysis we model the meso scale drift in two ways. The first parallels that of [10,11] with the Lagrangian velocity a-stable Lévy. The second and novel approach is to model the Lagrangian mesoscale acceleration as a-stable Lévy.…”
Section: Introductionmentioning
confidence: 94%
“…[2]. Randomly swimming microbes can often be modeled as a-stable Lévy motions [11]. Using the concept of directional preference put forth in [8], swimming in a preferential direction based on an energy gradient can be modeled using an operator-stable Lévy motion.…”
Section: Introductionmentioning
confidence: 99%
“…Hence for dilute concentrations of microbes swimming through a given fluid at standard conditions in an experimental flow cell, a probability distribution can be applied to describe the motility pattern. It has been observed that Levy motion defined by a-stable probability distributions of increments best describes the runs and tumbles of microbial motion [6,18,19]. The mixing measure within the definition of a Levy process may be employed to account for microbe food (energy) sources by skewing the movement along a gradient.…”
Section: Microbial Dynamicsmentioning
confidence: 98%
“…2 and 3). These interesting properties of the a-stable variables have found widespread use in a variety of fields, such as in the study of microbial dynamics [18,19], transport in porous media [29][30][31], anomalous dispersion [32], and super diffusion in turbulence [33][34][35].…”
Section: A-stable Levy Processes and Fadesmentioning
confidence: 99%
“…Processes with infinite MSD, such as α-stable Lévy motion, have been used to study nonlocal transport [18,19], movement patterns of marine predators [20], and microbial motion [21], to name a few examples. It can be shown that α-stable Lévy motion is 1/αself-similar [3] and therefore 1/α-diffusive on both the long and short time scales.…”
Section: A Infinite Msdmentioning
confidence: 99%